Legalitas Honorarium Advokat Dalam Hukum Positif dan Hukum Islam - Abrori, Abrori (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This article begins with the current legal aid phenomenon. Advocates as legal advisors and defenders of clients' interests in resolving legal cases. In an effort to resolve a legal case, advocates receive compensation/services for providing legal assistance in a case being faced by a client. This honorarium for advocates is certainly in the public spotlight nowadays, whether this honorarium has clear legality in positive law or Islamic law, because there are cases of advocates who do not comply with legal norms when defending several criminal cases. The research method is normative juridical, namely examining regulations and combining them with other theories as a tool in uncovering the problem of the legality of advocates' honorariums in the context of state law and Islamic law, especially with a statute approach. The findings in this research are that the legality of advocate honorariums is stated in the Compilation of Sharia Economic Law Article 307 and Law no. 18 Yr. 2003 concerning Advocates Articles 21 and 22 in terms of determining the costs of legal aid services. Because all of these legal bases stipulate that the determination of costs in the legal process with an advocate is based on an agreement between the client and the advocate. Keywords: Legality, Advocate Honorarium, Positive Law and Islamic Law.